Germinated Chickpea and Lupin as Promising Ingredients for Breadmaking—Rheological Features - Denisa Atudorei; Mădălina Ungureanu-Iuga; Georgiana Gabriela Codină; Silvia Mironeasa (Agronomy, 2021)
Improving the alpha-amylase activity of wheat flour represents an opportunity to valorize wheat grains of low baking quality. In this sense, germinated legumes can be used to increase enzymatic activity, giving superior final product characteristics at the same time. The aim of this study was to underline the effects of chickpea (CGF) and lupin germinated flours (LGF) added simultaneously to white wheat flour on the rheological behavior of dough and to evaluate an optimal product microstructure. For this purpose, the falling number, dough rheological properties during mixing, 3D-deformation and fermentation, and the visco-elastic behavior were evaluated, the effects of factors (CGF and LGF levels) and their optimization have been studied by applying a full factorial design and response surface methodology (RSM). The LGF sample had a composition of 39.4% protein, 10.3% moisture, 6.9% fat, and 3.4% ash, whereas the CGF presented 21.1 % protein, 9.4% moisture, 5.2% fat, and 3.6% ash. The results showed that CGF and LGF determined the decrease of the falling number, dough water absorption, tolerance to kneading, dough consistency at 250 and 450 s, extensibility, the maximum height of the gas release curve, volume of gas retained by the dough at the end of the test, total volume of CO2 production, visco-elastic moduli, and gelatinization temperatures. On the other hand, dough elasticity and alveograph curve ratio increased proportionally to the increase of CGF and LGF addition levels. The optimal combination considering the rheological properties of dough was found to be 8.57% CGF, 5.31% LGF, and 86.12% wheat flour, with enhanced alpha-amylase activity being obtained compared to the control. These results provide valuable information on the possibility of using germinated legumes such as chickpeas and lupin in breadmaking to enhance wheat flour technological properties (besides traditionally used barley malt flour).